EFEK PEMBERIAN BUAH MERAH (PANDANUS CONOIDEUS) TERHADAP PERUBAHAN HISTOPATOLOGIK GINJAL DAN HATI MENCIT PASCA PEMBERIAN PARACETAMOL - Suastika, Putu (Buletin Veteriner Udayana, 2012)
The aims of this study is determine the influence of Buah Merah (Pandanus conoideus)on histopathological changes in kidney and liver of mice caused by paracetamoladministration. This study used 30 famale mice were grouped into 5, so each group ofsix-sided tail. Body weight of mice ranged from 25 grams – 40 grams with the femalesex. Group K +, T1, T2, T3 all given 10 mg of paracetamol during seven continuous ,on the eighth day until day 29 groups T1, T2, and T3 given Buah Merah oil fell as muchas 0.3 cc, 0.6 cc and 0.9 cc respectively. Data obtained by scoring histological changesof kidney and liver organs. Results of kidney organ scoring average total for the groupof K + is 9.67, T1: 4.5, T2: 5.67 and T3: 7.17. The total scoring of liver for groups of K+ is 9.67, T1: 4.83, T2: 6, and T3: 8.33. Results Mean Kruskal-Wallis test for kidneyand liver showed that there were higler significant (P <0.05) between the positive control group (K +) with treatment group (T1, T2, and T3) it can prevent kidney andliver damage.
Keywords: Herbal Buah Merah, Paracetamol